(untitled) (Teacher Half-Yearly Journal, 2025)
The title of the study is "Unveiling the Realities: Understanding Sexual Harassment Perception among Secondary School Girls” in ward number 16 of Kathmandu Metropolitan City. For data collection, the schools were selected purposely inside Kathmandu i.e. Tarun Secondary School, Nepal Rastriya Secondary School and Yubak Secondary School of class 8 to 10 class. The schools were chosen from conventional purposive sampling method and the respondents were selected using census method. 320 female students were chosen from three secondary schools of KTM Ward No 16. The majority of respondents were between the ages of 16 to 18 which shows that they were in late adolescence. They were 100 out of the total 320 respondents. The psychological harassment was higher as compared to sexual harassment and economic harassment. Likewise, physical harassment also was found higher than sexual, economic and other types of harassment in the study area. The table indicates that response for physical harassment was 102, psychological harassment was 113, sexual harassment was 75, and economical and others was 25 and 5 respectively. Among them, 100 respondents had a loss of attention to studies and 95 respondents always felt stress. Likewise, 40 respondents said they had headaches and felt uneasy, 35 were feeling alone and 50 respondents said they had lost confidence. The sexual harassment activities were faced by 105 girls students by phone calls and social media whereas 95 respondents were showed vulgar things and frequently irritated, 35 respondents were tempted and proposed to sex, 50 respondents were attempted bad touch in sensitive organ and body parts, and lastly 35 respondents said vulgar words and whistling were used on them.